Analisa Efektifitas Pelatihan Bahasa Asing dengan Tingkat Kemampuan Beragam - Ari Setyorini (Humaniora, 2010)
This research is to measure foreign language study effectively from staffs in one directorate in various abilities. The methodology of this research is experiment method consists of 11 subject respondents with 3 different English level abilities. The experiment is done in combining the 3 levels in one class with the same level of difficulty for 3 months and 26 meetings. The data founded which will be analysed is placement test, mid-test, and final test data in quantitative. Meanwhile, qualitative data is gathered from observation result during training. From the observation, factors raising uneffective training are study motivation, self-efficacy and confidence level, and the needs for creating environment that supports foreign language learning so required ability could be improved.